FREQUENCY OF DEPRESSION AMONG PATIENTS WITH CHRONIC LIVER DISEASE - Khan, Adil Naseer; Abbassi, Mohammad Arshad; Gandapur, Asad; Alam, Aftab; Haroon, Muhammad Zeeshan; Hussain, Jawad (Journal of Ayub Medical College Abbottabad, 2020)
Background: Psychiatric co-morbidity is a frequent finding in patients with chronic liver disease (CLD). Patients with CLD may have anxiety, depression, sleep disturbances and behavioural disorders as well as cognitive defects. Therefore, this study was designed to determine the frequency of major depression in patients diagnosed with chronic liver disease Methods: This descriptive cross-sectional study was conducted at the department of gastroenterology Ayub Teaching Hospital Abbottabad from January-July 2017. One hundred and eleven patients diagnosed with chronic liver disease were included in the study using consecutive non-probability sampling technique. A detailed medical history was taken and physical exam was conducted before the patients were asked to answer a questionnaire (HADS-D). The answers were marked to obtain a final score. Quantitative variables like age, HADS-D score, and duration of CLD were described in terms of mean and standard deviation. Categorical variables like gender and depression were described in terms of frequencies and percentages. Stratification was done on age, duration of CLD and gender to see the effect modifiers. Chi-Square test was used at 5% significance level for determining statistically significant differences. Results: Out of 111 patients, 38 (34.2%) were found to have depression on the basis of their HADS-D score. When depression was stratified according to age, gender and duration of chronic liver disease, a strong statistical association was seen with the duration of chronic liver disease and increased serum ALT levels (p<0.05). Conclusion: Depression is fairly common in patients with CLD and is significantly associated with the duration of CLD and the derangement of liver enzymes.